Analysis of conglutin seed storage proteins across lupin species using transcriptomic, protein and comparative genomic approaches - Foley, R.; Jimenez-Lopez, J.; Kamphuis, L.; Hane, James; Melser, S.; Singh, K. (BioMed Central Ltd, 2015)
Background - The major proteins in lupin seeds are conglutins that have primary roles in supplying carbon, sulphur and nitrogen and energy for the germinating seedling. They fall into four families; α, β, γ and δ. Interest in these conglutins is growing as family members have been shown to have beneficial nutritional and pharmaceutical properties. Results - An in-depth transcriptome and draft genome from the narrow-leafed lupin (NLL; Lupinus angustifolius) variety, Tanjil, were examined and 16 conglutin genes were identified. Using RNAseq data sets, the structure and expression of these 16 conglutin genes were analysed across eight lupin varieties from five lupin species. Phylogenic analysis suggest that the α and γ conglutins diverged prior to lupin speciation while β and δ members diverged both prior and after speciation. A comparison of the expression of the 16 conglutin genes was performed, and in general the conglutin genes showed similar levels of RNA expression among varieties within species, but quite distinct expression patterns between lupin species. Antibodies were generated against the specific conglutin families and immunoblot analyses were used to compare the levels of conglutin proteins in various tissues and during different stages of seed development in NLL, Tanjil, confirming the expression in the seed. This analysis showed that the conglutins were expressed highly at the mature seed stage, in all lupin species, and a range of polypeptide sizes were observed for each conglutin family. Conclusions - This study has provided substantial information on the complexity of the four conglutin families in a range of lupin species in terms of their gene structure, phylogenetic relationships as well as their relative RNA and protein abundance during seed development. The results demonstrate that the majority of the heterogeneity of conglutin polypeptides is likely to arise from post-translational modification from a limited number of precursor polypeptides rather than a large number of different genes. Overall, the results demonstrate a high degree of plasticity for conglutin expression during seed development in different lupin species.